2021
DOI: 10.1128/mmbr.00031-20
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibility Group I1 (IncI1) Plasmids: Their Genetics, Biology, and Public Health Relevance

Abstract: Bacterial plasmids are extrachromosomal genetic elements that often carry antimicrobial resistance (AMR) genes and genes encoding increased virulence and can be transmissible among bacteria by conjugation. One key group of plasmids is the incompatibility group I1 (IncI1) plasmids that have been isolated from multiple Enterobacteriaceae of food animal origin and clinically ill human patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 207 publications
0
24
0
Order By: Relevance
“…We additionally analyzed the genomes of the recipient strains for plasmids of the same incompatibility complex as that of P2 (Incl1). No potentially incompatible plasmids were detected in the strains based on our BLAST analysis of the conserved replication initiation protein RepZ of IncI1 plasmids (35). Interestingly, subsequent surface mating of all P3 transconjugants with a naïve recipient E. coli strain ( E. coli W3110 tsr::kmR) further confirmed that conjugative P3 transfer was only possible for donor cells inheriting both P2 and P3 plasmids (Fig S4c).…”
Section: Resultsmentioning
confidence: 99%
“…We additionally analyzed the genomes of the recipient strains for plasmids of the same incompatibility complex as that of P2 (Incl1). No potentially incompatible plasmids were detected in the strains based on our BLAST analysis of the conserved replication initiation protein RepZ of IncI1 plasmids (35). Interestingly, subsequent surface mating of all P3 transconjugants with a naïve recipient E. coli strain ( E. coli W3110 tsr::kmR) further confirmed that conjugative P3 transfer was only possible for donor cells inheriting both P2 and P3 plasmids (Fig S4c).…”
Section: Resultsmentioning
confidence: 99%
“…19% of the species (nine out of 48) observed in the 56 sample-plasmid pairs were from the Pseudomonas genus, where P. fluorescens F113 and P. aeruginosa had the strong associations with pEK204. This was concerning because pEK204 has spread across pathogenic bacteria [26], and IncI1 plasmids like pEK204 promote AMR due to the presence of blaCTX-M, blaTEM, blaCMY and other ESBL genes [90][91]. We applied a novel approach of scaling the rate of pEK204-host PPIs by the level the pEK499-host PPIs, which identified numerous samples, especially ones with high numbers of pil operon genes.…”
Section: Discussionmentioning
confidence: 99%
“…19% of the species (nine out of 48) observed in the 56 sample-plasmid pairs were from the Pseudomonas genus, where P. fluorescens F113 and P. aeruginosa had the strong associations with pEK204. This was concerning because pEK204 has spread across pathogenic bacteria [26], and IncI1 plasmids like pEK204 promote AMR due to the presence of bla CTX-M, bla TEM, bla CMY and other ESBL genes [90-91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids are circular, double-stranded DNA molecules that occur naturally in bacterial cells [1], whose genes often provide evolutionary advantages for bacteria, such as antimicrobial resistance and/or virulence [2,3]. Plasmids are important vehicles in disseminating and acquiring antibiotic resistance and virulence, and can thus constitute a major burden on human health [4]. Recent studies have suggested that the prevalence of antimicrobial resistance (AMR) is higher in Low- and Middle-income Countries (LMICs) compared to European countries and the United States [5,6].…”
Section: Introductionmentioning
confidence: 99%